The key role of sulfation and branching on fucoidan antitumor activity - Oliveira, Catarina (2017)
There is an urgent need for antitumor bioactive agents with minimal or no side effects over normal adjacent cells. Fucoidan is a marine-origin polymer with known antitumor activity. However, there are still some concerns about its application due to the inconsistent experimental results, specifically its toxicity over normal cells and the mechanism behind its action. Herein, three fucoidan extracts (FEs) have been tested over normal and breast cancer cell lines. From cytotoxicity results, only one of the extracts shows selective antitumor behavior (at 0.2 mg mLâ 1), despite similarities in sulfation degree and carbohydrates composition. Although the three FEs present different molecular weights, depolymerization of selected samples discardedÂ MwÂ as the key factor in the antitumor activity. Significant differences in sulfates position and branching are observed, presenting FE 2 the higher branching degree. Based on all these experimental data, it is believed that these last two properties are the ones that influence the cytotoxic effects of fucoidan extracts.